Luminescence characteristics of individual Beijing haze aerosol particles. (October 2018) - Wang, Li; Bai, Zhangpeng; Pi, Yiqun; Zhai, Yadi; Zhang, Yinqi; Yan, Zhengguang; Ji, Yuan; Han, Xiaodong
Abstract: The rapid development of industrialization and urbanization has led to haze in Beijing that has garnered world attention. For the first time, we studied the luminescence properties of individual haze aerosol particles by using a scanning electron microscope (SEM) coupled with a cathodoluminescence (CL) spectrometer. CL analysis has rarely been reported for haze particles, however, we found that many haze particles showed varied luminescence characteristics. Many types of mineral dusts showed strong CL emission in the visible light wavelengths. Nitrogen-rich secondary particles had a strong CL emission in the UV wavelengths. Anthropogenic particles such as fly ash and Fe-rich, Ti-rich, and carbonaceous materials had much weaker CL responses. The mixture of mineral dusts and other species showed lower CL intensity and widened CL spectra, which continuously covered the UV-VIS-IR portion of the spectrum and which contrasted with the CL emissions of original mineral dusts and pure secondary salts. The sensitivity of CL spectra with respect to tiny changes in components, impurity, and valences enabled the CL spectroscopy to provide a unique perspective with which to analyze highly complicated mixtures of haze particles. Graphical abstract: Image 1 Highlights: Cathodoluminscence (CL) property of individual Beijing haze particles is measured. Mineral dusts show strong CL emission in visible light wavelength. Mixture of mineral dusts with other species show lowered and widened CL spectra. Nitrogen-rich secondary particles have a strong CL emission in the UV wavelength. Fly ash, Fe-rich, Ti-rich, and carbonaceous anthropogenic particles have weaker CL.